Case Report: SCN5A mutations in three young patients with sick sinus syndrome - Liang, Jiayu; Luo, Suxin; Huang, Bi (Frontiers in Cardiovascular Medicine, 2023)
Background Sick Sinus Syndrome (SSS) is generally regarded as a degenerative disease with aging; however, genetic mutations have been confirmed to be associated with SSS. Among them, mutations in SCN5A are common in patients with SSS. We report three young SSS patients with SCN5A mutations at different sites that have not been previously reported in Asian patients. Case presentation The three patients were all young females who presented with symptoms of severe bradycardia and paroxysmal atrial flutter, for which two patients received ablation therapy. However, after ablation, Holter monitoring indicated a significant long cardiac arrest; therefore, the patients received pacemaker implantation. The three patients had familial SSS, and genetic testing was performed. Mutations were found in SCN5A at different sites in the three families. All three patients received pacemaker implantation, resulting in the symptoms of severe bradycardia disappearing. Conclusion SCN5A heterozygous mutations are common among patients clinically affected by SSS. Their causative role is confirmed by our data and by the co-occurrence of genetic arrhythmias among our patients. Genetic testing for SSS cannot be performed as a single gene panel because of feasible literature results, but in presence of familial and personal history of SSS in association with arrhythmias can provide clinically useful information.